Flavocoxid Inhibits Phospholipase A2, Peroxidase Moieties of the Cyclooxygenases (COX), and 5-Lipoxygenase, Modifies COX-2 Gene Expression, and Acts as an Antioxidant - Bruce P. Burnett; Alessandra Bitto; Domenica Altavilla; Francesco Squadrito; Robert M. Levy; Lakshmi Pillai (Hindawi Limited, 2011)
The multiple mechanisms of action for flavocoxid relating to arachidonic acid (AA) formation and metabolism were studied in vitro. Flavocoxid titrated into rat peritoneal macrophage cultures inhibited cellular phospholipase A2 (PLA2) (IC50 = 60 μg/mL). In in vitro enzyme assays, flavocoxid showed little anti-cyclooxygenase (CO) activity on COX-1/-2 enzymes, but inhibited the COX-1 (IC50 = 12.3) and COX-2 (IC50 = 11.3 μg/mL) peroxidase (PO) moieties as well as 5-lipoxygenase (5-LOX) (IC50 = 110 μg/mL). No detectable 5-LOX inhibition was found for multiple traditional and COX-2 selective NSAIDs. Flavocoxid also exhibited strong and varied antioxidant capacities in vitro and decreased nitrite levels (IC50 = 38 μg/mL) in rat peritoneal macrophages. Finally, in contrast to celecoxib and ibuprofen, which upregulated the cox-2 gene, flavocoxid strongly decreased expression. This work suggests that clinically favourable effects of flavocoxid for management of osteoarthritis (OA) are achieved by simultaneous modification of multiple molecular pathways relating to AA metabolism, oxidative induction of inflammation, and neutralization of reactive oxygen species (ROS).